ANALISIS KESALAHAN STRUKTUR KALIMAT PADA PENERJEMAHAN BAHASA INDONESIA KE BAHASA JEPANG - Asep Achmad Muhlisian (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2019)
Translation in the process is a complex matter, so it is probable that in the translation process there are a lot of problems that can lead to translation errors. By using the case study research method (Case Study) the author tries to study, describe and sort out the syntax errors in the use of sentence structure that appear in the translation of Indonesian University of Education Japanese students' scientific papers. The results of data analysis showed that there were 45 errors found and many that appeared were form errors in sentence patterns, errors due to omission of parts of the sentence pattern, word order errors and errors added to the sentence pattern not to dominan.